Вынужденные колебания пологой цилиндрической оболочки с шарнирно опертыми и свободными краями - Бреславский, И. Д.; Аврамов, К. В. (НТУ "ХПИ", 2008)
Нелінійні коливання циліндричної панелі описуються рівняннями Донела-Муштарі-Власова. Аналітично знайдені точні моди лінійних коливань оболонки, які було використано для отримання дискретної моделі нелінійних коливань. Ця модель досліджена методом багатьох масштабів. Аналізується стійкість отриманих періодичних коливань за Ляпуновим.

Nonlinear oscillations of the cylindrical panel are described with the help of the Donnell-Mushtary-Vlasov equations. The exact modes of the linear oscillations of the shell were found analytically. These modes were used in order to obtain the discrete model of the nonlinear oscillations. This model was studied with the help of the multiple scales method. The Lyapunov stability of the periodical oscillation is studied.
Keywords: линейные колебания; резонанс; частота; расстройка; уравнения Доннела-Муштари-Власова